Prevotella copri-mediated caffeine metabolism involves ferroptosis of osteoblasts in osteoarthritis - Feng Li; Xin Wen; Pu Xue; Huiping Xu; Panyang Wu; Zhiming Xu; Xianwei Wang; Guofu Pi (Microbiology Spectrum)
ABSTRACT There is a positive causality between coffee consumption and osteoarthritis (OA); however, whether gut microbiota is involved needs to be discussed. Here, we observed that in caffeine consumers, fecal Prevotella copri abundance was positively correlated with subchondral bone mass, serum caffeine concentration was negatively correlated with bone mass, and fecal P. copri was negatively correlated with serum caffeine. In the OA model, caffeine intake aggravated articular cartilage destruction, bone mass loss, and intestinal barrier damage; on the contrary, paraxanthine intake reversed the above lesions. Importantly, after the intestinal P. copri supplement, caffeine-induced lesions in OA mice were effectively alleviated. Mechanically, P. copri has the potential to metabolize caffeine into paraxanthine, and this effect could alleviate the ferroptosis of osteoblast in the OA model. This study screened out that P. copri, an endogenous bacteria, has the ability to metabolize caffeine and revealed its effects on OA progression.IMPORTANCEThere is positive causality between coffee consumption and osteoarthritis (OA). Caffeine exposure is responsible for the reduction of bone mass and restrained osteoblast function. Prevotella copri abundance is exhausted in gut and positively correlated with subchondral bone mass in coffee consumption patients with OA. Supplement of intestinal P. copri alleviates caffeine-induced subchondral bone loss. P. copri has the potential to metabolize caffeine into paraxanthine, and this effect alleviates ferroptosis of osteoblast. Our study illustrated that intestinal P. copri possibly serves as a novel promising treatment for coffee consumers with OA.